USE OF MULTIPLE CHOICE TESTS IN MATHEMATICS - CHLADEK, Petr; SMETANOVA, Dana (Trends in education, 2015)
The paper concerns the case of multichoice tests in mathematics. We present the use of one of the e-learning part used by students of the combined form. The construction such a test is described here. Final part analyses successfulness of students and statistical evaluation of testing. In the paper there are presented the most common types of errors in tests. We discussed the appropriateness of this type of testing, especially for students of the combined form of higher education.
Keywords: testing of students; multiple choice tests; probability.